2018
DOI: 10.1111/ajt.14745
|View full text |Cite
|
Sign up to set email alerts
|

Donor kidney injury molecule-1 promotes graft recovery by regulating systemic necroinflammation

Abstract: Ischemia-reperfusion injury during kidney transplantation predisposes to delayed graft function, rejection, and premature graft failure. Exacerbation of tissue damage and alloimmune responses may be explained by necroinflammation: an autoamplification loop of cell death and inflammation, which is mediated by the release of damage-associated molecular patterns (eg, high-mobility group box-1; HMGB1) from necrotic cells that activate both innate and adaptive immune pathways. Kidney injury molecule-1 (KIM-1) is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 38 publications
3
21
0
Order By: Relevance
“…In a subsequent study, when we exposed donor kidneys from KIM-1 deficient mice to both warm and cold ischemia and then transplanted them into wild-type mice. In the same study, we observed greater renal and systemic inflammation as well as increased susceptibility to renal dysfunction and tissue damage, compared to transplanted kidneys from wild-type donors [18]. Taken together, these studies suggest that KIM-1 plays a protective role in mitigating tissue damage by inhibiting necroinflammation [18].…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…In a subsequent study, when we exposed donor kidneys from KIM-1 deficient mice to both warm and cold ischemia and then transplanted them into wild-type mice. In the same study, we observed greater renal and systemic inflammation as well as increased susceptibility to renal dysfunction and tissue damage, compared to transplanted kidneys from wild-type donors [18]. Taken together, these studies suggest that KIM-1 plays a protective role in mitigating tissue damage by inhibiting necroinflammation [18].…”
Section: Introductionsupporting
confidence: 62%
“…We chose this time point based on the literature and sustained viability of recipient mice [26]. The primary outcome was renal function at 2 days and was quantified by serum creatinine as previously described [18]. We chose this timepoint as peak graft injury and mortality occurs within the first 3 days of surgery if the graft fails [26].…”
Section: Renal Transplantation/aim Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, necroinflammation has been found to be involved in primary and distant organ injury following acute kidney injury [58, 59]. However, the role of necroinflammation in intestinal I/R, especially links with ferroptosis, remains unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies may need to be conducted to elucidate intrinsic mechanisms of the IIR ALI. Firstly, necroinflammation has been found to be involved in distant organ injury [ 26 , 27 ]. The activated innate immune system has been reported to initiate local inflammation and subsequently lead to necroinflammation in remote organs via spreading damage-associated molecular patterns and cytokines to the systemic circulation from primary ischemic organs [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%